Etika Pembelajaran Perspektif KH. Hasyim Asy'ari dan Implementasinya di Pondok Pesantren - Uswatun Hasanah; Siti Khomsiyati (TAFAHUS: JURNAL PENGKAJIAN ISLAM, 2022)
Learning ethics is an important aspect that must exist and be implemented in learning activities so that the internalization of knowledge by students can be successful. This study aims to describe the implementation of ethics learning in Adab Al-'lim wa Al-Muta'allim by KH. Hasyim Asy'ari at the Way Jepara Darussalamah Islamic Boarding School, East Lampung. This research is qualitative and descriptive. Methods of data collection in this study include interviews, observation, and documentation. Furthermore, to check the validity of the author's data using triangulation. The results showed that the implementation of ethics learning in Adab Al-'lim wal Al-Muta'allim by KH. Hasyim Asy'ari at Way Jepara Darussalamah Islamic Boarding School, East Lampung, has shown good results. This is because educators and students have implemented ethical values in learning activities, supported by strict Islamic boarding school policies in giving prohibitions, sanctions, and even rewards to students. Besides implementing learning ethics in Adab Al-'lim wa Al-Muta'allim by Hasyim Asy'ari at Way Jepara Darussalamah Islamic Boarding School, East Lampung, in a routine lesson that discusses the book Adab Al-'lim wa Al-Muta'allim by KH. Hasyim Asy'ari. The inhibiting factors in the implementation of ethics learning consist of two factors, namely, internal factors and external factors. The internal factors are self-learning intention and the heredity factor. The external factors are the negative influence of electronics and inadequate security systems. So it can be concluded learning ethics can be implemented properly because of exemplary and supportive institutional policies.